Engaging dialogically with auditory hallucinations: design, rationale and baseline sample characteristics of the Talking With Voices pilot trial. Issue 4 (2nd October 2021) - Longden, Eleanor; Corstens, Dirk; Pyle, Melissa; Emsley, Richard; Peters, Sarah; Chauhan, Nisha; Dehmahdi, Nikki; Morrison, Anthony P.
ABSTRACT: Aims : The Talking With Voices pilot trial assesses feasibility and acceptability of a novel dialogical intervention to ameliorate distress associated with auditory hallucinations. The results will inform a definitive randomised trial to assess clinical and cost-effectiveness of the intervention. Method : The trial is single-site with a single-blind (rater) design in which adult participants with a diagnosis of schizophrenia-spectrum disorder are randomised to receive either treatment as usual (TAU), or TAU plus up to 26 sessions of Talking With Voices therapy over six months. Participants are assessed at baseline and again at six-month follow-up. The primary outcomes are quantitative and qualitative assessments of feasibility and acceptability amongst patients and healthcare staff. Secondary outcomes will involve clinical measures, including targeted instruments for voice hearing, dissociation, and emotional distress. Results : Recruitment figures and baseline characteristics of the sample are reported (N=50). Conclusions : The Talking With Voices pilot trial aims to extend the evidence-base for interventions which use techniques such as dialogue, formulation and trauma-informed working to improve relationships between hearer and voice. Current findings demonstrate that recruitment and treatment allocation targets were met. If shown to be acceptable, the intervention may provide new therapeutic options for voice hearers with a diagnosis of psychosis.